The Hyaluronic Acid–HDAC3–miRNA Network in Allergic Inflammation - Kim, Youngmi; Eom, Sangkyung; Park, Deokbum; Kim, Hyuna; Jeoung, Dooil (Frontiers in Immunology, 2015)
We previously reported the anti-allergic effect of high molecular weight form of hyaluronic acid (HMW-HA). In doing so, HA targets CD44 and inhibits FcεRI signaling and cross-talk between epidermal growth factor receptor (EGFR) and FcεRI. We previously reported the role of histone deacetylases (HDACs) in allergic inflammation and allergic inflammation-promoted enhanced tumorigenic potential. We reported regulatory role of HA in the expression of HDAC3. In this review, we will discuss molecular mechanisms associated with anti-allergic effect of hyaluronic acid in relation with HDACs. The role of microRNAs (miRNAs) in allergic inflammation has been reported. We will also discuss the role of miRNAs in allergic inflammation in relation with HA-mediated anti-allergic effects.